2008
DOI: 10.12973/ejmste/75352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mastery Learning Approach on Secondary School Students’ Physics Achievement

Abstract: This study aimed at finding out the effects of Mastery Learning Approach (MLA) on students' achievement in Physics. The study was Quasi-experimental and Solomon Four Non-equivalent Control Group Design was used. The target population comprised of secondary school students in Kieni East Division of Nyeri District. The accessible population was Form Two students in district coeducational schools in the division. Purposive sampling was used to obtain a sample of four coeducational secondary schools. Each school p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…These results are also in line with those of several previous studies [9,10,11,12,17,19,21], where MLS improved students' understanding of basic concepts in entrepreneurship education. In addition, several authors [13,14,15,16] agree that the use of a diversity of learning strategies in entrepreneurship education provide an encouraging environment and interesting, interactive, and effective learning climate for minority students.…”
Section: Analysis and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are also in line with those of several previous studies [9,10,11,12,17,19,21], where MLS improved students' understanding of basic concepts in entrepreneurship education. In addition, several authors [13,14,15,16] agree that the use of a diversity of learning strategies in entrepreneurship education provide an encouraging environment and interesting, interactive, and effective learning climate for minority students.…”
Section: Analysis and Discussionsupporting
confidence: 92%
“…The teachers of the two classes had almost equivalent in term of experience and same level of qualifications. In addition, a double-blind method was used whereby the teachers and students involved in this study were not informed of the experiment being conducted [20]. The independent variable was the method of instruction (MLS vs. TLA), while the dependent variable was the students' academic achievement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can further be suggested that the science process skills emphasized in this study might have assisted the experimental groups to perform better in chemistry than the control groups. Studies carried out by Khan et al (2011);Opara (2011);Wambugu & Changeiywo (2008);Alexander (2001); Mao & Chang (1998) and Ertepinar & Geban (1996) showed that inquiry-based teaching approaches enhanced students' achievement in science subjects, which are in agreement with the findings of this study. Mandor (2002) and Ibe (2004) research findings were also in agreement with the findings of this study by indicating that active participation of the students in science lessons contributed to effective learning.…”
Section: Discussionsupporting
confidence: 91%
“…The second is the Mastery for Learning Group-Based Approach which was presented in the Carroll learning model (1968;cited in Damavandi et al, 2010) and says that classroom learning is a timebased phenomenon and the longer time of learning lead to the higher rate of learning. This method in comparison with the traditional training, in the different science courses such as physics (Wambugu & Chageiywo, 2008), chemistry (Damavandi et al, 2010), mathematics (Shafi e, et al, 2010 has been more successful. The researches have shown that combination of these two methods have completed each other and have more effects on the academic achievements (Baker et al, 1989;Mevareach, 1986) and mental abilities (Krank & Moon, 2001).…”
Section: Introductionmentioning
confidence: 99%